1984
DOI: 10.1002/path.1711430205
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular basis of damage to the human urinary bladder induced by irradiation

Abstract: The effects of x-irradiation on the subcellular structure of the human urinary bladder were investigated by electron microscopic examination of biopsies taken during check cystoscopies from 25 patients between 1 month and 22 years after completion of a course of therapeutic radiation. All tissues of the bladder wall were damaged to some extent by the treatment. In the urothelium this was reflected by the development of more than the usual numbers of lysosomes and autophagic vacuoles in all cell layers. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…26,27 The second phase is the infiltration of inflammatory cells. [26][27][28] The third phase is chronic and is associated with collagen deposition and developing fibrosis. 26,27,29 Some studies reported that animal urinary bladder damage induced by a single dose of radiation had pathological changes that included epithelial denudation and focal hyperplasia with ulceration, 26 changes in axon profiles and mast cell density, 27 and increased formation of superoxide free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The second phase is the infiltration of inflammatory cells. [26][27][28] The third phase is chronic and is associated with collagen deposition and developing fibrosis. 26,27,29 Some studies reported that animal urinary bladder damage induced by a single dose of radiation had pathological changes that included epithelial denudation and focal hyperplasia with ulceration, 26 changes in axon profiles and mast cell density, 27 and increased formation of superoxide free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, MN/PGs and small cells with high N/C ratios have been reported in residual tumor tissues during recurrent growth of tumors. 71,72 Neosis as the Mechanism of Self-Renewal in Tumor Cells. The process of self renewal in cancer cells occurs through a low frequency of tumor initiating cells the precursors of which are thought to be constantly maintained as cancer stem cells in the tumor cell population.…”
Section: Neosismentioning
confidence: 99%
“…Rats irradiated with 20 Gy all exhibited small and contracted bladders 6 mo after treatment (19,40). In human bladders, subepithelial fibrosis became more extensive with time after irradiation (1). The loss of bladder muscle and damage to vascular endothelial cells and bladder neurons was also evident (39).…”
mentioning
confidence: 99%